Prevention of Corruption Crimes Through Anti-Corruption Education and Pancasila Morals - Wijayanti, Maggie Amaliza (Journal of Creativity Student, 2019)
Corruption is a very deviant act, dangerous and detrimental. This action is carried out by abusing a position that has been trusted by many people. And this action is a selfish act because it is only for self-interest. Corruption is a deviant behavior or crime that is socially and legally prohibited. The problem of corruption in Indonesia is increasingly rampant starting from the central government, regional government, which is very detrimental to the life of the Indonesian nation and state, this causes people to think that politics justifies all means. This requires an effective corruption eradication and prevention strategy. By establishing Anti-Corruption Education and Pancasila Citizenship Education. Youth must be given a mindset of the dangers of corruption and play an active role in preventing corruption. The implementation of anti-corruption education is carried out by studying problems related to corruption which consists of four parts, namely problems, alternative policies, proposed solutions and part of the action plan. This activity is so that students will acquire some desired attitudes such as honesty, discipline, responsibility, hard work, humility, courage and justice. This education should be focused on activities and processes that are productive, creative, skill development, personality, integration, excellence, moral and spiritual. Implementation of Anti-Corruption Education aims to be able to develop positive values in students. Through this education, you can develop good character and personality values. By establishing the Anti-Corruption Education movement and Pancasila Citizenship Education, it is hoped that it will help the process of eradicating and preventing corruption by the Indonesian Corruption Eradication Commission.